2017
DOI: 10.1111/mpp.12584
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of two homeodomain transcription factors with critical but distinct roles in virulence in the vascular pathogen Verticillium dahliae

Abstract: Vascular wilt caused by Verticillium dahliae is a destructive disease that represents a chronic economic problem for crop production worldwide. In this work, we characterized two new regulators of pathogenicity in this species. Vph1 (VDAG_06555) was identified in a candidate gene approach as a putative homologue of the transcription factor Ste12. Vhb1 (VDAG_08786), identified in a forward genetics approach, is similar to the homeobox transcription factor Htf1, reported as a regulator of conidiogenesis in sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 72 publications
0
33
0
Order By: Relevance
“…dahliae , several studies have concluded that melanin accumulation is not required for virulence in V . dahliae in hosts such as tobacco, tomato and lettuce (Wang et al ., ; Sarmiento‐Villamil et al ., ; Sarmiento‐Villamil et al ., ), but another study demonstrated that deletion of V . dahliae VdPKS1, a key factor for melanin production, resulted in reduced virulence on cotton (Zhang et al ., ).…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…dahliae , several studies have concluded that melanin accumulation is not required for virulence in V . dahliae in hosts such as tobacco, tomato and lettuce (Wang et al ., ; Sarmiento‐Villamil et al ., ; Sarmiento‐Villamil et al ., ), but another study demonstrated that deletion of V . dahliae VdPKS1, a key factor for melanin production, resulted in reduced virulence on cotton (Zhang et al ., ).…”
Section: Discussionmentioning
confidence: 96%
“…In M. oryzae, melanin is necessary for the strengthening of the appressorium wall prior to host penetration but this phenomenon has not been so clearly demonstrated in other pathogenic fungi producing appressoria, such as Alternaria alternata (Jacobson, 2000). In V. dahliae, several studies have concluded that melanin accumulation is not required for virulence in V. dahliae in hosts such as tobacco, tomato and lettuce (Wang et al, 2018;Sarmiento-Villamil et al, 2018a;Sarmiento-Villamil et al, 2018b), but another study demonstrated that deletion of V. dahliae VdPKS1, a key factor for melanin production, resulted in reduced virulence on cotton . Undoubtedly, gene deletion studies of various MAPK cascade components suggest a strong correlation between melanin biosynthesis and virulence in V. dahliae (Tzima et al, 2010;Tian et al, 2014;Tian et al, 2016;Wang et al, 2016;Yu et al, 2019;Zheng et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations